Dystocia in a buffalo due to a foetal monster accompanying hydrops amnii - SATHYA, A; MAHAJAN, AMIT; PRABHAKAR, S (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to a foetal monster with catlin mark accompanied by hydrops amnii in a buffalo and its delivery by caesarean section is being reported in this communication.